The influence of social media short videos on Indonesians' English acquisition - Rakhmasari, Dwi Lia; Pratiwi, Berlin Insan (Universitas Muhammadiyah Purwokerto, 2024)
Social media is able to make an individual can get information, entertainment even jobs easily from their home. Learning language through social media become popular method for some people. Most famous social media platforms like Instagram, YouTube and TikTok use short video to give entertainment toward internet users. Using short video in social media tent learners to have unintentional or unplanned learning since many uses the applications almost every day. This study explained the impact of short video features on social media toward Indonesian English acquisition. It used a descriptive qualitative design. Descriptive qualitative design is research designed to obtain information about current status phenomena. The respondents consist of 494 Indonesian from different age 13-15 y.o, 16-18 y.o, 19-25 y.o, 26-35 y.o, >35 y.o Once the data was collected, all the answers were reviewed and analyzed, and conclusions formulated. This research found out that TikTok become the most popular application for Indonesian in the age 13-25 y.o followed by Instagram YouTube. Instagram become the most popular application for Indonesian in the age 26- > 35 y.o followed by TikTok and YouTube. This study found out that Indonesian believe the most significant impact toward their English are vocabularies. 94,1% respondents said that they get a lot of vocabularies from the video. 87.9% respondents said that since they get a lot of vocabularies from the video it is helpfull for themto easily understand about what they read. Besides, 87.4% respondents said that they improve their speaking skill after watching short video. 83,6 % respondent said that they imitate what they hear from the short video on social media and unconsciously improve their listening skill after watching short video. The last, 69.8% respondents believe that their writing improve.